2014
DOI: 10.14800/ics.229
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of Cystatin C in Acute Coronary Syndromes: Something More Than a Marker of Renal Function?

Abstract: Serum cystatin C (Cys-C) levels perform better than other markers of renal function as indicator of cardiovascular outcome both in population-based studies and in patients with non-ST-elevation acute coronary syndrome (NSTE-ACS). Whether the relation between elevated serum Cys-C levels and risk of a worse cardiovascular prognosis reflects a more precise measurement of renal function or an association with nonrenal factors such as inflammation is a matter still poorly defined. In a prospective, multicenter stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“… 39 Reports showed that Cys C is mainly used as a reliable biomarker of kidney function and would help to identify patients at risk of cardiac dysfunction, thus predicting further cardiovascular events. 36 , 40 , 41 Fabjan et al revealed that a high level of Cys C was positively associated with the increased risk of cardiovascular morbidity and mortality, which could be used for the detection of new onset or deteriorating CVD. 42 In our study, consistent with literature reports, it was shown that the level of Cys C in the patients of CHD was obviously higher than in the control group and was positively correlated with the degree of coronary artery stenosis, more specific but less sensitive, and the smallest AUC.…”
Section: Discussionmentioning
confidence: 99%
“… 39 Reports showed that Cys C is mainly used as a reliable biomarker of kidney function and would help to identify patients at risk of cardiac dysfunction, thus predicting further cardiovascular events. 36 , 40 , 41 Fabjan et al revealed that a high level of Cys C was positively associated with the increased risk of cardiovascular morbidity and mortality, which could be used for the detection of new onset or deteriorating CVD. 42 In our study, consistent with literature reports, it was shown that the level of Cys C in the patients of CHD was obviously higher than in the control group and was positively correlated with the degree of coronary artery stenosis, more specific but less sensitive, and the smallest AUC.…”
Section: Discussionmentioning
confidence: 99%
“…population-based studies and in patients with non-ST-elevation acute coronary syndrome [110]. Therefore CysC is an ideal biomarker for study the renal function in SCD patients which is ongoing hemolysis and inflammation secondary to the sickling phenomenon and in which creatinine clearance is generally increased and serum creatinine is low.…”
Section: Hematology -Latest Research and Clinical Advancesmentioning
confidence: 99%